A-41 years old male with alcoholic cardiomyopathy at Tabanan General Hospital, Bali-Indonesia: a case report - Gede Wikananda; Eka Ariawan; Ary Priadnyana (Intisari Sains Medis, 2019)
Background: Alcoholic cardiomyopathy is a form of toxic cardiomyopathy which develops as a result of long-standing chronic ingestion of alcohol. Its clinical findings share similar features to other forms of dilated cardiomyopathy. Diagnosis can be made based on the history of long term alcohol abuse, clinical findings, and supporting diagnostic studies. This case report aims to overview alcoholic cardiomyopathy; from establishing the initial diagnosis to the treatment given for the condition.Case Description: A 41 years old male came to the emergency department unit with shortness of breath since last few days. Shortness of breath was said to be getting worse over time and progressed to breathlessness at rest. Other complaints were palpitations, fatigue, and long-standing cough. The patient was found to have a history of drinking alcohol in large quantities since 27 years ago. The blood pressure was 110/70 mm Hg, pulse rate 105 beats/min, and respiratory rate was 20 breaths/min. Slight edemas on both legs were also found.  From auscultation examination, bibasilar crepitation on both lungs was found. Cardiac examination showed systolic murmur of mitral regurgitation (MR) and tricuspid regurgitation (TR).  On supporting investigation, a chest x-ray showed cardiomegaly (cardiothoracic ratio; 57%). ECG examination showed sinus tachycardia and left atrial (LA) and left ventricular (LV) enlargement. Trans-thoracal echocardiographic (TTE) examination revealed; RWMA: global hypokinetic-akinetic, multi-chamber dilated and severe LV systolic dysfunction (EF 29%) and diastolic function (Grade IV (E/A Ratio>4)). Valve examination showed moderate-severe MR and moderate TR (TVG 40 mmHg).Conclusion: Alcohol cardiomyopathy is one of the most common causes of heart failure in young age and carries a poor prognosis if not treated properly. Treatment of alcoholic cardiomyopathy mainly includes total alcohol abstinence along with drugs used to treat systolic heart failure to reverse the condition and correct any nutritional deficiencies.